2008
DOI: 10.1039/b803265n
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal chemical genetics for swift lead and target identification

Abstract: Reciprocal chemical genetics: correlation between chemical profile of in vivo phenotypes and in vitro data of potential target genes leads to swift target identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Because of its considerable mass in the body, skeletal muscle may constitute a convenient and abundant source of stem cells, and thus has received considerable recent attention for its potential in cellular and cell‐mediated therapies (Passier et al , 2003). Muscle‐derived stem cells (MDSCs) can be isolated from skeletal muscles (Seale et al , 2001), and have been shown to differentiate toward several different lineages in vitro and in vivo in response to genetic manipulation, changes in the extracellular environment or stimulation with intrinsic regulators or factors, including growth factors and other signalling molecules (Stocum, 2004; Jackson et al , 2009; Kuijl et al , 2008). Thus, the recent interest in using MDSCs as a source material for cell therapy is perhaps not surprising.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its considerable mass in the body, skeletal muscle may constitute a convenient and abundant source of stem cells, and thus has received considerable recent attention for its potential in cellular and cell‐mediated therapies (Passier et al , 2003). Muscle‐derived stem cells (MDSCs) can be isolated from skeletal muscles (Seale et al , 2001), and have been shown to differentiate toward several different lineages in vitro and in vivo in response to genetic manipulation, changes in the extracellular environment or stimulation with intrinsic regulators or factors, including growth factors and other signalling molecules (Stocum, 2004; Jackson et al , 2009; Kuijl et al , 2008). Thus, the recent interest in using MDSCs as a source material for cell therapy is perhaps not surprising.…”
Section: Introductionmentioning
confidence: 99%